Fun Surveys? Developing an Innovative Approach to Assessing Learning Through Citizen Science - Allf, Bradley; Larson, Lincoln; Goodwin, Jean; Dunn, Robert; Cooper, Caren (Citizen science : theory and practice, 2025)
Assessing the impact of citizen science participation on volunteers is increasingly important. However, traditional methods for evaluating volunteer experiences—such as quantitative surveying—have drawbacks. Response rates are often low, pre- and post-tests provide a coarse metric for assessing learning, and static evaluation techniques have failed to align with the participatory spirit of citizen science, where volunteers are involved in understanding their role in scientific inquiry. In response to these problems, we developed a more engaging type of longitudinal survey aimed at achieving higher response rates and better involving volunteers in understanding the scientific value of their survey efforts. We first reviewed the literature on “fun” and found that fun activities embody six characteristics: autonomy, social connection, playfulness, challenge, transport, and curiosity. We used this “fun heuristic” to design “SciQuest,” an exploratory survey tool that evaluated volunteers’ pro-environmental attitudes and behaviors across citizen science projects hosted on the platform SciStarter.org. SciQuest proved to be a reliable instrument that captured common learning outcome–related constructs measured by conventional, validated instruments. Although most beta-testers had no preference between SciQuest and a conventional survey, among those expressing a preference, nearly twice as many favored SciQuest. SciQuest also achieved much higher retention rates (49–67%) than past conventional surveys on SciStarter (19%). Embedded, creative approaches to citizen science evaluation are thus a viable, and perhaps preferable, complement to traditional surveys, particularly on citizen science platforms. Citizen science facilitators should extend their volunteer-centric perspectives to include participant evaluation and seek evidence-based strategies for enriching the citizen science experience.